Resistance to insecticides in Bemisia tabaci and Trialeurodes vaporariorum (Homoptera: Aleyrodidae) in Colombia y Ecuador - CARDONA, CÉSAR; RENDÓN, FRANCISCO; GARCÍA, JAVIER; LÓPEZ-AVILA, ARISTÓBULO; BUENO, JUAN M.; RAMÍREZ, JOSÉ D. (Revista Colombiana de Entomología, 2001)
Trialeurodes vaporariorum (Westwood) and the A and B biotypes of Bemisia tabaci (Gennadius) are the most important whiteflies affecting annual crops in Colombia and Ecuador. Levels of resistance to organophosphate, carbamate, and pyrethroid insecticides in adults of these species were studied across 40 locations in Colombia and Ecuador. Using the vial technique, line base data and CL50 and CL50 values were calculated for methamidophos, methomyl, and cypermethrin under laboratory conditions. Diagnostic dosages were established and these were used to monitor resistance in the field, also using the vial technique. Corrected mortalities at diagnostic dosages were compared by means of the analysis of variance. T. vaporariorum exhibited low resistance to methomyl, high resistance to methamidophos in most locations studied, and intermediate to high resistance to cypermethrin in 9 locations. The B biotype of B. tabaci was very resistant to methomyl in 9 of 10 locations sampled and highly resistant to methamidophos across the region known as the Atlantic Coast of Colombia. It showed intermediate resistance to cypermethrin in 3 locations in the Atlantic Coast. insecticide resistance levels are discussed in relation to the difficulties in managing whiteflies in the Andean zone. Baseline data for T. vaporariorum for carbofuran, lambda• cyhalothrin, and imidacloprid are presented for future reference.